What is The Association Between Honeycombing Appearance on CT and Life Expectancy in Patients with Scleroderma? A Comprehensive Systematic Review - I Dewa Gede Satwika Putra; Wyka Faulani Hafizah Nur (The International Journal of Medical Science and Health Research, 2026)
Background: Systemic sclerosis (SSc) is a chronic autoimmune connective tissue disease with high morbidity and mortality, primarily driven by interstitial lung disease (ILD). Honeycombing on computed tomography (CT) represents irreversible fibrotic lung damage, but its precise relationship with life expectancy remains incompletely defined. Methods: This systematic review synthesized evidence from 80 studies (198 individual cohorts in the primary meta-analysis) examining the association between honeycombing appearance on CT and survival outcomes in SSc patients. Data extraction focused on honeycombing assessment methods, patient characteristics, survival statistics, hazard ratios (HRs), and confounding factors. Results: Honeycombing prevalence in SSc-ILD cohorts ranged from 37.2% to 41.9%, with higher frequency in limited cutaneous SSc. The systematic review by Haekal Mahargias et al. (2026) demonstrated that honeycombing was associated with a 2- to 3-fold increased mortality risk, with HRs ranging from 1.72 (95% CI 1.38–2.14) to 4.64 (95% CI 1.68–12.81). This association persisted after adjusting for age, gender, pulmonary function tests, and scleroderma subtype. Landini et al. (2022) found honeycombing extent was an independent predictor of respiratory mortality but not overall mortality. Radiographic progression (≥2% increase in quantitative ILD scores) predicted worse long-term survival (p=0.014 after adjustment). Baseline forced vital capacity (FVC) ≥70% was a strong protective factor (OR=0.039, 95% CI 0.002–0.616, p=0.02). Discussion: Honeycombing represents irreversible fibrotic damage that outperforms ground-glass opacities in prognostic value. The association with mortality is partially mediated by pulmonary function decline, particularly FVC. Methodological heterogeneity in honeycombing assessment limits definitive conclusions. Current therapies (nintedanib, cyclophosphamide, mycophenolate) stabilize lung function but do not reverse established honeycombing. Patients with extensive honeycombing (≥50% lung involvement) are often excluded from therapeutic trials, creating selection bias. Conclusion: Honeycombing on CT is a significant independent predictor of increased mortality in SSc-ILD, particularly respiratory-specific death. Standardized CT scoring systems with validated inter-rater reliability are urgently needed. Future prospective studies should examine honeycombing progression dynamics and develop honeycombing-specific therapeutic algorithms.